2020
DOI: 10.3390/jcm9103309
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis Associated with Viral Hepatitis: Systematic Review

Abstract: Background: We conducted a systematic review in order to summarize the available data on pancreatitis associated with viral hepatitis. Methods: A comprehensive literature search of Medline, Scopus and ISI Web of Science databases was conducted and papers eligible for the inclusion identified. Results: In total, 46 studies reporting data on 73 patients were included in the analysis. Most of the cases were diagnosed in Asia (57.53%), followed by North America (23.29%), and Europe (13.70%). Most of the patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
(66 reference statements)
0
13
0
2
Order By: Relevance
“…Regarding the indirect mechanism, SARS-CoV2 causes microthrombi formation due to its ability to invade endothelial cells via the ACE2 protein. This phenomenon is also observed in other virus infections, such as viral hepatitis[ 85 ]. Microthrombus in vasculature triggers hypoperfusion of the pancreas, resulting in ischemic pancreatitis.…”
Section: Discussionmentioning
confidence: 61%
“…Regarding the indirect mechanism, SARS-CoV2 causes microthrombi formation due to its ability to invade endothelial cells via the ACE2 protein. This phenomenon is also observed in other virus infections, such as viral hepatitis[ 85 ]. Microthrombus in vasculature triggers hypoperfusion of the pancreas, resulting in ischemic pancreatitis.…”
Section: Discussionmentioning
confidence: 61%
“…The most common cause was hepatitis E (4 patients), with hepatitis B confirmed in only 1 case [ 27 ]. In a recent systematic review, Panic et al reported 73 published cases of AP in patients with viral hepatitis, 6 of whom (8.2%) had HBV [ 28 ]. Interestingly, the only reported case of chronic pancreatitis associated with viral hepatitis was due to HBV.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the only reported case of chronic pancreatitis associated with viral hepatitis was due to HBV. Since both HBsAg and HCV antigens were detected in pancreatic tissue, the authors hypothesized that chronic infection with HBV or HCV viruses might also affect the pancreas [ 28 ]. In 1988, Alexander et al compared HBsAg+ and HBsAg− liver transplantation patients.…”
Section: Discussionmentioning
confidence: 99%
“…Einzelne Fallkontrollstudien zeigen Assoziationen verschiedener Erkrankungen mit einer Risikoerhöhung für eine akute Pankreatitis, deren Kausalität jedoch unklar ist. Hierzu zählen eine Pneumokokken-Infektion, chronisch-entzündliche Darmerkrankungen sowie eine Hepatitis A (Evidenzlevel 3) [43][44][45][46]. Ebenfalls unklar ist die Datenlage hinsichtlich eines Zusammenhangs zwischen Ernährung und Pankreatitisrisiko: 2 populationsbasierte Kohortenstudien zeigen eine Risikoreduktion für eine akute, nicht biliär-bedingte Pankreatitis durch eine fischreiche Ernährung (2-3 Portionen/Woche) und eine gemüsereiche Ernährung, ein direk-ter kausaler Zusammenhang bzw.…”
Section: Weitere Seltene Ursachen Und Ernährungseinflüsseunclassified